The death of gold in early Visayan societies ethnohistoric accounts and archaeological evidences - Estrella, Victor (2016)
Access online through this link: https://journals.upd.edu.ph/index.php/asp/article/view/5493/4927
Keywords: Archaeological surveying; Ethnohistory; Interment